A critical review of drug testing policy in the Philippines. (May 2022) - Dioquino, Carissa Paz; Gerona, Roy Roberto
The drug policy in the Philippines is written as the Comprehensive Dangerous Drugs Act of 2002 or Republic Act 9165. Unlike drug policies in other countries, the law includes policies on drug testing. Aside from mandatory drug testing for specific situations, the law states further that two testing methods should be employed—a screening test, and a confirmatory test to be performed if the former yields a presumptive positive result. Over 1000 drugs of abuse screening laboratories are scattered all over the Philippines, but only seven can perform confirmatory testing using either gas chromatography-mass spectrometry (GC-MS) or liquid chromatography-mass spectrometry (LC-MS) technologies. In the last 30 years, more sophisticated analytical technologies like liquid chromatography-tandem mass spectrometry (LC-MS/MS) and high-resolution mass spectrometry such as liquid chromatography-quadrupole time-of-flight mass spectrometry (LC-QTOF/MS) have been developed not only to confirm what has been detected on screening tests, but also to determine the presence of new psychoactive substances that are not usually detected in drug screening. New matrices are also being utilized for the detection of drugs. The drug testing policy in the Philippines will have to keep up with the changing drug trends and drug testing innovations in the world to truly address the current administration's war on drugs. With the adoption of new drug testing methods using modern analytical platforms, the cut-offs used for drug testing interpretation should be updated.